Numerical Investigation of PDC Cutter – Rock Interaction using LS-DYNA and Design of Experiment - Americo, Paulo Faife Inocencio (IRC, 2020)
To be able to predict how a certain process will happen before it happens is the trend in all the industry, enables one to be prepared for the future. In this line of thinking the current work is an attempt to simulate the drilling operation to understand the rockcutter interaction with the aim of optimizing the conditions to reduce the cutting force process. The Simulation was conducted in LS-DYNA, where the cutter was treated as rigid tungsten carbide and the rock as sandstone. The rock was stationary, and the cutter was treated to move at constant speed, with fixed rake angle and cutting depth. Variable such as cutting speed, bake rake angle, depths of cut and friction coefficient were being changed in a scientific manner to study the effect of the parameters on the cutting force. The result showed that LS-DYNA simulate the rock cutting process with accuracy. From the results the most important factors affecting the cutting force are rake angle and depth of cut. From examination of the results, the ones that uses the least force have rake angle of 0 and depth of cut of 0.5mm, the optimum combination of rake angle and depth of cut would optimize the drilling process. What makes this work unique is the application of Design of Experiment (DOE) to deeply study how the parameters affect the cutting force and which parameters affect the process the most.